(untitled) (The Review of Diabetic Studies, 2025)
Background: Type 2 diabetes mellitus is commonly associated with dyslipidaemia, peripheral neuropathy, and impaired quality of life despite standard pharmacological therapy. Non-pharmacological interventions such as meditation may provide additional metabolic and neurophysiological benefits. Aims & Objectives: To evaluate the effect of Sahaja Yoga meditation on glycaemic control, lipid profile, sensory nerve conduction, and quality of life in patients with Type 2 Diabetes Mellitus. Methods: A comparative interventional study was conducted on 200 patients with Type 2 Diabetes Mellitus aged 30–50 years, divided into cases practicing Sahaja Yoga meditation and controls receiving routine medical care. The intervention group practiced supervised Sahaja Yoga weekly with twice-daily home practice for six months. Fasting blood glucose, HbA1c, lipid profile, sensory nerve conduction parameters, and WORLD HEALTH ORGANIZATION QUALITY LIFE –BREF (brief version ) (WHOQOL-BREF ) scores were assessed at baseline, three months, and six months. Results: The Sahaja Yoga group showed significant reductions in fasting blood glucose and HbA1c, along with favorable changes in lipid profile, including decreased total cholesterol, LDL cholesterol, and triglycerides, and increased HDL cholesterol. Sensory nerve conduction parameters improved significantly, with reduced latency and increased amplitude and conduction velocity. Quality of life improved across all WHOQOL-BREF domains. No significant changes were observed in controls. Conclusions: Sahaja Yoga meditation is a safe and effective adjunct to conventional therapy in Type 2 Diabetes Mellitus, improving metabolic control, peripheral nerve function, and quality of life.